The Application of Scout Education System in Mathematics Learning To Improve Student Mathematical Disposition - Fitriana Eka Chandra (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2019)
Mathematics has always been a difficult subject for the students. Math learning in the classroom is often a very tedious process for most students. Many students are unmotivated to study mathematics, which means that the disposition of students in learning mathematics is lacking. Mathematical dispositions relate to student attitudes, the tendency to think and act positively in learning mathematics. One of the extracurricular activities that students are interested in is the Extrakurikuler Scout activities. Students are always eager to follow the activities in these activities. This means that the education system contained in the Boy Scouts is able to attract students' attention and be able to motivate students. Even when students are given difficult challenges, students seem to be passionate and happy to follow the challenge. This means students have a positive attitude in following Scout activities. This is certainly when applied in the learning of mathematics will be able to make students feel happy to attend math lessons. So that in the end can make students' mathematics learning outcomes for the better. Keyword: Math lesson, Scout, math disposision